In-situ synthesis of melanin in tumor with engineered probiotics for hyperbaric oxygen-synergized photothermal immunotherapy. (December 2022) - Xiao, Yi; Wang, Dongdong; Luo, Ban; Chen, Xue; Yao, Yuzhu; Song, Cheng; Wu, Meichan; Li, Puze; Li, Xuyu; Zhang, Hong; Zhu, Xiaohua; Yang, Xiangliang; et al.
Abstract: Anaerobic bacteria and facultative anaerobe are usually used as delivery carriers of antitumor drugs because of their tumor hypoxia targeting and antitumor immune activation abilities, but suffer from dose-dependent systemic side effects. Here, engineered probiotics Nissle 1917 (EcN-T) were constructed for in-situ synthesis of melanin in tumor region for enhanced photothermal therapy (PTT) combining with immunotherapy. By means of genetic engineering, EcN-T that could highly express tyrosinase under near-infrared (NIR) light irradiation were constructed. Due to their intrinsic tumor hypoxia targeting, EcN-T could accumulate and rapidly proliferate in tumor region after intravenous injection. Tyrosinase expression for the following melanin biosynthesis within tumor could be initiated upon NIR exposure. Hyperbaric oxygen treatment facilitated the oxidation of tyrosine to promote the generation of melanin in situ, giving robust photothermal performance to induce immunogenic tumor cell death. Assited by immunostimulatory responses of EcN, maturation of dendritic cells and priming of cytotoxic T cells were largely promoted in tumor tissue, resulting in significant inhibition of tumor growth and recurrence. This bacteria-mediated combined therapeutic strategy showed high efficacy and good safety. Graphical Abstract: By means of genetic engineering and synthetic biology, engineered probiotics Nissle 1917 (EcN-T) which show excellent tumor targeting and proliferation abilities are constructed for in-situ synthesis of melanin in tumor region induced by NIR light irradiation and HBO treating. Upon light exposure, considerable heat can be generated to induce immunogenic tumor cell death. Assited by immunostimulatory responses of EcN, maturation of dendritic cells and priming of cytotoxic T cells are largely promoted in tumor tissue, giving significant inhibition of tumor growth and recurrence. ga1 Highlights: Engineered probiotics Nissle 1917 can intracellularly produce melanin with excellent photothermal performance. Engineered probiotics Nissle 1917 can rapidly proliferate and homogenously distribute in tumor region. Melanin biosynthesis within tumor can be initiated upon external NIR exposure. Hyperbaric oxygen can promote the generation of melanin within tumor.